Mutation Analysis and Single Nucleotide Polymorphism of TP53 Gene in Breast Cancer in East Java - Rizqa Radhiyah; I Kade Karisma Gita Ardana; Wisnubroto Wisnubroto; Dwi Listyorini; Hendra Susanto (Journal of Tropical Life Science, 2021)
The Incidence of Indonesia breast cancer case in 2018 was reported at 20.7% or 160,653 in number. The factors that caused breast cancer is TP53 gene mutation and Single Nucleotide Polymorphism (SNP). This study aimed to determine the mutation and Single Nucleotide Polymorphism (SNP) of TP53 gene in breast cancer. Samples of this study were 9 people chosen based on a purposive technique. The methods include total DNA isolation, DNA quantification, PCR, and sequencing. The results of the sequencing were then analyzed using alignment and blast. The SNP is browsed by the SNP finder on NCBI both followed by protein modeling. The results of this study indicate the existence of mutation in the exon and intron regions. Substitution of Guanine (G) to base Adenine (A) is occur in codon 496 which is a coding region. SNP was also obtained in exon of sample 12. The conclusion of this study is breast cancer can be caused by mutations that occur in the exon and altered the structur of protein structure, so then affect the binding affinity between p53 and its target domain. Tp53 gene mutation is not the only cause of breast cancer staging development, there are other genes that also contribute to the development of cancer stage. In addition, Single Nucleotide Polymorphism in the TP53 gene can be used as a predisposition marker of breast cancer that has potential to be inherited